Genetic control and expression of the major ejaculatory bulb protein (PEB-me) in Drosophila melanogaster. - Ludwig, M.Z.; Uspenskii, I.Y.; Ivanov, A.I.; Kopantseva, M.R.; Dianov, C.M.; Tamarina, N.A.; Korochkin, L.I. (Biochemical Genetics, 1991)
PEB-me is a predominant protein of mature Drosophila melanogaster ejaculatory bulbs. It is resolved into four or five closely spaced subfractions (apparent molecular weight 35-39 kD) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Four electrophoretic variants of PEB-me differing in apparent molecular weight by 200-800 daltons were found. These appear to be controlled by four alleles of a gene (peb) located by recombination and deletion mapping to the 60F1-2 region of chromosome 2. A minor ejaculatory bulb protein of ca. 80 kD (hPEB) was found to be immunochemically related to PEB and possibly encoded by peb. PEB is not detected by immunoblotting techniques in virgin females, in male tissues other than the ejaculatory bulb, or during developmental stages preceding the formation of this organ. The results of transplantations of genital imaginal discs and of immature ejaculatory bulbs between two strains having different PEB alleles suggest that the ejaculatory bulb is the site of PEB synthesis. In flies mutant for tra, tra-2, dsx, or ix, tissue specificity of PEB localization is retained and the protein is found whenever the ejaculatory bulb is formed, regardless of the chromosomal sex of the fly. The protein is transferred into the female genital duct during mating, where it can be detected for up to 12 hr. Possible functions of PEB in Drosophila reproduction are discussed.